Helping patients with paranoid and suspicious thoughts: A cognitive-behavioural approach - Freeman, D; Garety, P (2006)
Paranoid and suspicious thoughts are a significant clinical topic. They regularly occur in 10-15% of the general population, and persecutory delusions are a frequent symptom of psychosis. In the past, patients were discouraged from talking about paranoid experiences. In contrast, it is now recommended that patients are given time to talk about them, and cognitive-behavioural techniques are being used to reduce distress. In this article we present the theoretical understanding of paranoia that underpins this transformation in the treatment of paranoid thoughts and summarise the therapeutic techniques derived. Emphasis is placed on the clinician approaching the problem from a perspective of understanding and making sense of paranoid experiences rather than simply challenging paranoid thoughts. Ways of overcoming difficulties in engaging people with paranoid thoughts are highlighted.